2020
DOI: 10.1001/jamainternmed.2019.4717
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcome of Implantable Cardioverter/Defibrillator Lead Failure

Abstract: hort compared with outpatients in the study by Edelman et al 1 may have masked a comparably smaller effect of opioids.A strength of our study is the higher homogeneity of patients regarding the indication of opioid treatment (cancer pain). Despite the great efforts of Edelman et al 1 to control confounders, opioid use in veterans with and without HIV infection is a powerful surrogate for a large range of detrimental health conditions (opioid use for musculoskeletal and bone diseases with decreased mobility 4 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Policy makers could establish a national postmarket registry for medical devices (eg, as implemented in Iceland) and invest in programs for active surveillance (eg, as modeled by the San Francisco National Institutes of Health-funded postmortem monitoring of sudden cardiac death). 58,59 The FDA has signaled an interest in active surveillance methodologies, funding prospective studies for an active surveillance registry of implantable vascular-closure devices and supporting the National Evaluation System for health Technology (NEST). 60,61 Such platforms could help address the regulatory gaps exposed by Penumbra.…”
Section: Limits Of Postmarket Surveillancementioning
confidence: 99%
See 1 more Smart Citation
“…Policy makers could establish a national postmarket registry for medical devices (eg, as implemented in Iceland) and invest in programs for active surveillance (eg, as modeled by the San Francisco National Institutes of Health-funded postmortem monitoring of sudden cardiac death). 58,59 The FDA has signaled an interest in active surveillance methodologies, funding prospective studies for an active surveillance registry of implantable vascular-closure devices and supporting the National Evaluation System for health Technology (NEST). 60,61 Such platforms could help address the regulatory gaps exposed by Penumbra.…”
Section: Limits Of Postmarket Surveillancementioning
confidence: 99%
“…Improved adherence to postmarket obligations will require better processes for reporting and evaluation. Policy makers could establish a national postmarket registry for medical devices (eg, as implemented in Iceland) and invest in programs for active surveillance (eg, as modeled by the San Francisco National Institutes of Health–funded postmortem monitoring of sudden cardiac death) …”
Section: Renewing the Call For Regulatory Reformmentioning
confidence: 99%
“…Despite these measures, there are increasing concerns regarding the current postmarketing surveillance system. Passive surveillance has been reported to underestimate malfunction of cardiac electronic devices that results in death . A report published by the International Consortium of Investigative Journalists estimated that nearly 2 million injuries and 80 000 deaths associated with medical devices occurred between 2008 and 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Passive surveillance has been reported to underestimate malfunction of cardiac electronic devices that results in death. 6,7 A report 8 published by the International Consortium of Investigative Journalists estimated that nearly 2 million injuries and 80 000 deaths associated with medical devices occurred between 2008 and 2017. Postmarketing trials were reported to often have design limitations that hindered their ability to be of clinical use.…”
mentioning
confidence: 99%
“…In this issue of JAMA Internal Medicine , 2 reports illustrate the importance of an improved surveillance system, particularly for life-sustaining medical devices. In one report, Davidsson et al present the nationwide experience of Iceland with the Riata defibrillator lead (St Jude Medical), which was recalled in 2011 because of the risk of serious injury or death. The study adds to prior experience about adverse events with the Riata lead .…”
mentioning
confidence: 99%